The Corellation of Forward Head Posture With Dynamic Balance to Student Members of the Umsida Sports UKM - Anjasmara, Bagas; Arti, Widi; Mulyadi, Soffil Yudha (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2023)
Forward head posture (FHP) is a type of postural that is generally described with the head tilted anteriorly/front. The wrong posture like FHP can affect the condition of certain body parts. The point of the Center of Gravity that moves will cause an uneven distribution of body weight and will disrupt the line of gravity which is a biomechanical component of the body’s balance. HoweverGood body balance can be obtained by doing regular physical activity and exercise. This study aims to find out whether or not there is a correlation between forwarding head posture conditions and disruption of dynamic balance in individuals who are actively exercising. In this study, the design used was a cross-sectional approach. The measurement of the degree of forward head posture uses the craniovertebral angle, while the measurement of dynamic balance uses the Modified Bass Test. In the results of the correlation test with Spearman’s Rank, the correlation coefficient value (sig.2-tailed) was 0.361 with a confidence interval (alpha) of 0.05 for the 2-sided test. With a significance of 0.361> 0.05, it shows that the Forward Head Posture condition does not have a significant relationship with Dynamic Balance in Umsida Sports UKM Students.